Diabetes‐free survival after extended distal pancreatectomy and islet auto transplantation for benign or borderline/malignant lesions of the pancreas. Issue 3 (23rd January 2019) - Balzano, Gianpaolo; Maffi, Paola; Nano, Rita; Mercalli, Alessia; Melzi, Raffaella; Aleotti, Francesca; De Cobelli, Francesco; Magistretti, Paola; Scavini, Marina; Secchi, Antonio; Falconi, Massimo; Piemonti, Lorenzo
Abstract : Islet autotransplant is particularly attractive to prevent diabetes after extended pancreatectomy for benign or borderline/malignant pancreas disease. Between 2008 and 2018, 25 patients underwent left extended pancreatectomy (>60%) and islet autotransplant for a neoplasm located in the pancreatic neck or proximal body. Overall, disease‐free and diabetes‐free survivals were estimated and compared with those observed in 68 nondiabetic patients who underwent distal pancreatectomy for pancreatic neoplasms without islet autotransplant. Median follow‐up was 4 years. We observed no deaths and a low morbidity (nonserious procedure‐related complications in 2 of 25 patients). Patient and insulin‐independent survival rates at 4 years were 100% and 96%, respectively. Glucose homeostasis remained within a nondiabetic range at all times for 19 (73%) of 25 patients. Preoperative glycemic level and insulin resistance were major predictors of diabetes development in these patients. Patients undergoing islet autotransplant had a longer diabetes‐free survival than did patients without islet autotransplant ( P = .04). In conclusion, islet autotransplant after extended pancreatic resection for neoplasms is a safe and successful procedure for preventing diabetes. Abstract : This study demonstrates the feasibility, efficiency, and safety of autologous islet transplantation for the prevention of surgical diabetes after extended pancreatic resection for pancreatic diseases other than chronic pancreatitis.